Rebranding Label Kemasan Sebagai Sarana untuk Meningkatkan Brand Awareness Usaha Mikro Kecil dan Menengah (UMKM) Frozen Food Mas Fian di Kelurahan TuriKota Blitar - Gideon Setyo Budiwitjaksono; Putri Indah Rachmawati; Muhammad Yafie Alfiandy; Rizky Riza Ismail; Mochammad Syahris Sauki (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
The large number of frozen food business competitors for micro and macro entrepreneurs demands that businesses continue to increase innovation. As a frozen food MSME, Mas Fian focuses on building brand equity so that the business can survive. MSME frozen food Mas Fian believes in rebranding packaging labels as a means to increase brand awareness. The purpose of this study was to understand the effect of rebranding packaging labels on increasing Brand Awareness of Frozen Food Mas Fian Micro, Small and Medium Enterprises (MSMEs). More specifically, this study aims to find out how packaging labels can increase Mas Fian's MSME frozen food brand awareness before and after the packaging label rebranding process. This research method uses descriptive and verification methods. This research was conducted on consumers who buy or consume Frozen Food Mas Fian products. This label rebranding activity is expected to increase sustainable brand awareness, easily recognized and embedded in the hearts of consumers, which can influence repurchase intentions and purchase decisions.